INVESTIGATION OF THE SOLID MINERAL DEPOSITS IN KANO STATE'S SCHIST BELT USING GEOCHEMICAL ANALYSIS (FUDMA JOURNAL OF SCIENCES, 2022)
This paper uses geochemical analysis to investigate solid mineral deposits in Kano state's schist belt. A number of geophysical studies have recently focused on the area, with one of them estimating the causative body parameters through modeling of ground magnetic data collected in the study area; a follow-up study like this is thus required. Using an Agilent Microwave Plasma-Atomic Emission Spectrometer (MP-AES), eight rock samples from the study area were prepared for geochemical analysis. The study area was discovered to be rich in iron, chromium, aluminum, silicon, calcium, potassium, zinc, and manganese, with mean values of 157.10, 6.35, 274.71, 324.76, 27.83, 239.79, 25.49, and 160.20 ppm, respectively. Muscovite, Fuchsite, Biotite, Chlorite, and Quartz are schist minerals rich in these elements. Gold and silver were also discovered, although in small quantities, with mean values of 0.15 and 0.03 ppm, respectively. It is recommended that government and other stakeholders in the solid mineral industry should explore the study area in order to exploit these resources. It is also recommended that a radiometric study be conducted in the area to determine the presence of thorium and uranium, as well as the area's safety from radioactive hazards due to the high amount of potassium recorded.
Keywords: Geochemical Analysis, Kano State’s Schist belt, MP-AES, Solid Minerals